2013
DOI: 10.1063/1.4807084
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical effects on energy transfer in disordered open quantum systems

Abstract: Exact mapping between system-reservoir quantum models and semi-infinite discrete chains using orthogonal polynomials Journal of Mathematical Physics 51, 092109 (2010) We explore various design principles for efficient excitation energy transport in complex quantum systems. We investigate energy transfer efficiency in randomly disordered geometries consisting of up to 20 chromophores to explore spatial and spectral properties of small natural/artificial LightHarvesting Complexes (LHC). We find significant stati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…3,4 Previous research has found that maximal transport efficiency will be obtained at a finite dephasing rate when dephasing noise is beneficial to the system and has quantified the optimal dephasing rate as a function of both dissipation and sink coupling strength. 2 The current work extends previous studies 2,4,[18][19][20] by examining the relationship between the coupling strength between chromophores and the optimal dephasing rate. We demonstrate that not only does an optimal dephasing rate exist in both one-and two-dimensional networks but also that it increases in magnitude with increasing coupling strength between chromophores.…”
Section: Introductionsupporting
confidence: 58%
“…3,4 Previous research has found that maximal transport efficiency will be obtained at a finite dephasing rate when dephasing noise is beneficial to the system and has quantified the optimal dephasing rate as a function of both dissipation and sink coupling strength. 2 The current work extends previous studies 2,4,[18][19][20] by examining the relationship between the coupling strength between chromophores and the optimal dephasing rate. We demonstrate that not only does an optimal dephasing rate exist in both one-and two-dimensional networks but also that it increases in magnitude with increasing coupling strength between chromophores.…”
Section: Introductionsupporting
confidence: 58%
“…As regards the role of decoherence in the mixing time of both discrete-time and continuous-time quantum walks, especially for chains, cycles and hypercubes, a review appears in [21]. Moreover, in the context of light-harvesting phenomena, the role of geometry has also been investigated in terms of structure optimization [53], in the presence of disordered systems [54,55], and to propose design principles for biomimetic structures [56].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has generally gone under the name of noise-assisted transport (NAT). In this context, the role of geometry has been theoretically analyzed in terms of structure optimization [16], in the case of disordered systems [17], and also for the proposal of design principles for biomimetic structures [18]. Therefore, the possibility to experimentally reproduce NAT effects in purely optical networks with controllable parameters and topology, would allow one to verify the predictions of NAT models in simple test systems.…”
mentioning
confidence: 99%